Documentation of indigenous knowledge on medicinal plants used to manage common influenza and related symptoms in Luwero district, central Uganda - Katuura, E.; Omujal, F.; Tumusiime, R. H.; Nabukalu, D.; Byamukama, R. (Journal of Medicinal Plants Research, 2016)
Herbs are used in treatment of various diseases in Uganda. Influenza is one of the diseases that is treated by herbs, the disease previously known to be non fatal is progressively becoming a threat due to immune complications in people living with HIV, poor diets and the fear of fatal introduced strains like Bird Flu. An ethno botanical survey was conducted to document medicinal plants and preparations used in the management of influenza and related symptoms in Luwero, Central Uganda. Information was obtained using questionnaires, focus group discussions, key informant interviews, direct observations in households and field excursions. Information on plants/parts used, method of preparation, mode of administration, commonly used formulations and their dosages was documented. Twenty nine medicinal plants distributed in 17 families were documented; Mangifera indica family Anacardiaceae, Ocimum basilicum L., (Lamiaceae), Psidium guajava L. (Mytaceae) and Mormodica feotida L. (Curcubitaceae) were the commonly used plants respectively. The leaves were the most used part of the plants while decoctions were the commonly used method of preparation and the oral route was the main mode of administration. Antimicrobial assay and nutritional profile of some formulae is underway to standardize formulae that can be used against respiratory infections at household level.